Experimental study of informal rewards in peer production. - Michael Restivo (Public Library of Science (PLoS), 2012)
We test the effects of informal rewards in online peer production. Using a randomized, experimental design, we assigned editing awards or "barnstars" to a subset of the 1% most productive Wikipedia contributors. Comparison with the control group shows that receiving a barnstar increases productivity by 60% and makes contributors six times more likely to receive additional barnstars from other community members, revealing that informal rewards significantly impact individual effort.